South American leafhoppers of the tribe Typhlocybini (Hemiptera: Cicadellidae: Typhlocybinae) - Christopher H. Dietrich (Zoologia (Curitiba), 2013)
The fauna of Typhlocybini (sensu stricto, excluding Empoascini) endemic to South America is reviewed and comprises seven closely related genera, five described herein as new, and 55 species, 52 here described as new. The genera and species are described and keys and illustrations are provided to aid in their identification. Columbonirvana Linnavuori comprises 17 species, 16 new. Eualebra Baker comprises 19 species, 17 new. Euzyginella gen. nov., comprises four new species. Neozyginella gen. nov., comprises six new species. Pseudhadina gen. nov., comprises one new species. Pseudozyginella gen. nov., comprises three new species. Tahurella gen. nov., comprises five new species. One new synonym is recognized: Eualebra smithii Baker, 1899 equals Dikraneura (Hyloidea) reticulata Osborn, 1928, syn. nov. One previously described species placed in Eualebra belongs in tribe Dikraneurini; thus, a new combination is proposed: Alconeura (Hyloidea) rubra (Van Duzee), comb. nov. Most of the specimens available for this study were from Malaise trap and canopy fogging samples obtained at very few localities in Bolivia, Brazil, Colombia, Ecuador, and Peru, suggesting that further sampling in South America, particularly in the Amazonian rainforest and eastern foothills of the Andes Mountains, will reveal large numbers of additional species.